GPCRomics of Homeostatic and Disease-Associated Human Microglia - Hsiao, Cheng-Chih; Sankowski, Roman; Prinz, Marco; Smolders, Joost; Huitinga, Inge; Hamann, Jörg (Frontiers in Immunology, 2021)
G-protein-coupled receptors (GPCRs) are critical sensors affecting the state of eukaryotic cells. To get systematic insight into the GPCRome of microglia, we analyzed publicly available RNA-sequencing data of bulk and single cells obtained from human and mouse brains. We identified 17 rhodopsin and adhesion family GPCRs robustly expressed in microglia form human brains, including the homeostasis-associated genes CX3CR1, GPR34, GPR183, P2RY12, P2RY13, and ADGRG1. Expression of these microglial core genes was lost upon culture of isolated cells ex vivo but could be acquired by human induced pluripotent stem cell (iPSC)-derived microglial precursors transplanted into mouse brains. CXCR4 and PTGER4 were higher expressed in subcortical white matter compared to cortical grey matter microglia, and ADGRG1 was downregulated in microglia obtained from normal-appearing white and grey matter tissue of multiple sclerosis (MS) brains. Single-cell RNA sequencing of microglia from active lesions, obtained early during MS, revealed downregulation of homeostasis-associated GPCR genes and upregulation of CXCR4 expression in a small subset of MS-associated lesional microglia. Functional presence of low levels of CXCR4 on human microglia was confirmed using flow cytometry and transwell migration towards SDF-1. Microglia abundantly expressed the GPCR down-stream signaling mediator genes GNAI2 (αi2), GNAS (αs), and GNA13 (α13), the latter particularly in white matter. Drugs against several microglia GPCRs are available to target microglia in brain diseases. In conclusion, transcriptome profiling allowed us to identify expression of GPCRs that may contribute to brain (patho)physiology and have diagnostic and therapeutic potential in human microglia.